Optimalisasi Kasir Dan Minimisasi Biaya Studi Kasus Pada Swalayan PSFJ Di Jakarta Selatan - Yanti Budiasih (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2015)
Service systems, particularly those related to customer service, an institution faced with the problem of how to provide the best service to the customer. At a service system, generally a queue of customers who ask to be served. In operations research theory, there is one device that can be used to solve the problems of the queue, the queue model. This study aims to find answers to the problems faced by a queue of supermarkets in Depok, namely PSFJ. In that context too, the issue that always arises is whether these facilities economically sufficient, if no improvement system then the cost will be lower or not.